Fundamentals of Mechanics - Chandra, Suresh; Sharma, Mohit Kumar; Sharma, Monika (New Delhi : Foundation Books, 2014)
Fundamentals of Mechanics is a textbook intended for first year students of physics at undergraduate level. It deals with the principles and applications of mechanics which is taught as a core subject of physics. The range of topics covered in this book includes Galilean transformation, Newton's law of gravitation, vectors, centre of mass, moment of inertia and angular momentum. There are many review questions which are ideal for homework assignments. Moreover, the book is thoroughly illustrated with numerous figures to help demonstrate the key concepts. Key features:Provides detailed explanation of the basic concepts of mechanics; Includes solved examples and chapter-end exercises comprising both descriptive and non-descriptive questions; Contains 250 exercises of varying difficulties, from simple to difficult calculations.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).